The Distributional Impact of Taxes and Social Spending in Croatia - Inchauste, Gabriela; Rubil, Ivica (World Bank, Washington, DC, 2017)
This paper describes the impact of fiscal policy on inequality and poverty, and examines recent policy changes and whether there is room for an increased role for fiscal policy in improving the well-being of the poor. Taxes and social spending reduced inequality in Croatia; however, once the impacts of indirect taxes are considered, the system is unable to reduce poverty, especially for families with children and retirees. Beginning in the second decile, households are net payers to the treasury, as the share of taxes paid exceeded the cash benefits received for all but the poorest 10 percent of the population. Microsimulations of recent tax changes find that inequality after taxes and transfers is expected to increase slightly in 2017, as most of the benefits of the reform were concentrated at the top of the distribution. Although the impact of lower value-added taxes on electricity and utility bills is expected to be slightly poverty reducing, this effect is small relative to the relief that is needed. A reduction in the standard value-added tax rate from 25 to 24 percent would result in a small decline in poverty and inequality. However, the impact may be much smaller, depending on how this measure would be financed.